1996
DOI: 10.1046/j.1365-2567.1996.d01-718.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of MHC class I‐restricted cytotoxic T lymphocytes by expression of a viral protein in muscle cells: antigen presentation by non‐muscle cells

Abstract: Expression of reporter genes in muscle cells has been achieved by intramuscular (i.m.) injection of plasmid DNA expression vectors. We previously demonstrated that this technique is an effective means of immunization to elicit both antibodies capable of conferring homologous protection and cell‐mediated immunity leading to cross‐strain protection against influenza virus challenge in mice. These results suggested that expression of viral proteins by muscle cells can result in the generation of cellular immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
0
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(111 citation statements)
references
References 34 publications
(43 reference statements)
4
105
0
2
Order By: Relevance
“…Such APC did not need to be transfected themselves. [16][17][18] The presence of the foreign antigen ␤-gal in the lymph nodes was a first hint for induction and generation of an immune response. The generation of a specific humoral immune response against the encoded protein after genetic immunization was seen for every site of injection, but the titers were influenced by the injection site.…”
Section: -Induced Immune Responses To Different Lacz Plasmid Expressimentioning
confidence: 99%
See 1 more Smart Citation
“…Such APC did not need to be transfected themselves. [16][17][18] The presence of the foreign antigen ␤-gal in the lymph nodes was a first hint for induction and generation of an immune response. The generation of a specific humoral immune response against the encoded protein after genetic immunization was seen for every site of injection, but the titers were influenced by the injection site.…”
Section: -Induced Immune Responses To Different Lacz Plasmid Expressimentioning
confidence: 99%
“…Thus, bone marrow-derived nonmuscle cells were shown to be involved in the induction of cytotoxic T lymphocytes (CTL) following intramuscular DNA immunization. [16][17][18] In contrast, the skin and mucous membranes are the physiological sites where most exogenous antigens are normally encountered. The skin-associated lymphoid tissues contain specialized cells such as keratinocytes, macrophages and Langerhans' cells, which are involved in the initiation and further augmentation of immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, only few bone marrow-derived antigen-presenting cells (APCs), 3,4 especially dendritic cells (DCs) that perform a critical step in the induction of primary immune responses, are directly transfected by injected DNA, 5,6 leading to deficient presentation of peptides from endogenously synthesized antigens on major histocompatibility complex (MHC) molecules. Studies of stably transfected myoblasts, [7][8][9] reconstitution of SCID mice with allogeneic bone marrow-derived APCs after DNA vaccination, 4 and surgical ablation of the injection site, 10 as well as skin excision/grafting experiments 11 also indicate a role for transfected myocytes and keratinocytes in DNA-initiated immune responses. However, these studies demonstrate that acquisition of antigens released from transfected myocytes or keratinocytes and cross-presentation by DCs are essential to induce T-cell responses for any DNA vaccination strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was subsequently shown that only professional antigen-presenting cells (APC) could actually prime immune responses with DNA vaccines. [7][8][9][10] While direct transfection of APC is not absolutely essential, 11 it is probable that some APC are transfected and antigen expression in these APC primes MHC class I and II responses. This may account for the strong immune responses induced by DNA vaccines, especially considering the extremely small quantities of antigen expressed from typical doses of plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%